Notes on the Selection and Care of Polar Footwear - Croft, Andrew; Roberts, Brian (Polar Record, 1940)
The choice of footwear is still one of the most outstanding problems which confront a traveller in the polar regions. Differences of opinion have arisen for various reasons, but perhaps the most common one is lack of experience of the available types. Personal views are influenced by the nature of the journeys already undertaken, the climatic conditions and the types of country experienced, whether the individual has had to repair his own footwear or has had native help, whether he has good circulation, the question of whether his feet are subject to excessive perspiration, and whether he has any tendency to flat-footedness, etc. It must also be remembered that a man who has used a particular kind of footwear in unsuitable conditions or without proper care tends to condemn that kind as being useless in all circumstances.